How Does AI Enable Surgical Quality Improvement? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
The integration of artificial intelligence (AI) into the surgical field represents a paradigm shift in modern healthcare, promising to elevate the standards ...
Keywords: AI in Surgery and Robotics; Enable; Surgical; Quality; Artificial Intelligence; Machine Learning; Healthcare